Midwives׳ decision making about transfers for 'slow' labour in rural New Zealand. Issue 6 (June 2015) - Patterson, Jean; Skinner, Joan; Foureur, Maralyn
Abstract Midwives who provided Lead Maternity Care (LMC) to women in rural areas were invited to share their experiences of decision making around transfer in labour. Ethics approval was obtained from the NZ National Ethics Committee. Objective to explore midwives׳ decision making processes when making transfer decisions for slow labour progress from rural areas to specialist care. Design individual and group interviews were conducted with a purposive sample of rural midwives. The recalled decision processes of the midwives were subjected to a content and thematic analysis to expose experiences in common and to highlight aspects of probabilistic (normative), heuristic (behavioural), and group decision making theory within the rural context. Setting New Zealand. Participants 15 midwives who provided LMC services to women in their rural areas. Findings 'making the mind shift', 'sitting on the boundary', 'timing the transfer' and 'the community interest' emerged as key themes. The decision processes were also influenced by the woman׳s preferences and the distance and time involved in the transfer. Key conclusions and implications for practice the findings contribute insights into the challenge of making transfer decisions in rural units; particularly for otherwise well women who were experiencing slow labour progress. Knowledge of the fallibility of our heuristic decision making strategies may encourage the practitioner to step back and take a more deliberative, probabilistic view of the situation. In addition to the clinical picture, this process should include the relational and aspirational aspects for the woman, and any logistical challenges of the particular rural context.